P04.50 Doxycycline impairs mitochondrial function and protects human glioma cells from hypoxia-induced cell death: implications of using Tet-inducible systems. (19th September 2018) - Sauer, B; Luger, A; Lorenz, N I; Engel, A L; Braun, Y; Voss, M; Harter, P N; Steinbach, J P; Ronellenfitsch, M W
Abstract: Background: Inducible gene expression is an important tool in molecular biology research to study protein function. Most frequently, the antibiotic doxycycline is used for regulation of so-called tetracycline (Tet)-inducible systems. In contrast to stable gene overexpression, these systems allow investigation of acute and reversible effects of cellular protein induction. Recent reports have already called for caution when using Tet-inducible systems as the employed antibiotics can disturb mitochondrial function and alter cellular metabolism by interfering with mitochondrial translation. Reprogramming of energy metabolism has lately been recognized as an important emerging hallmark of cancer and is a central focus of cancer research. Therefore, the scope of this study was to systematically analyze dose-dependent metabolic effects of doxycycline on a panel of glioma cell lines with concomitant monitoring of gene expression from Tet-inducible systems. Material and Methods: Experiments were performed with the human cell lines LNT229, G55, U343MG and SVG. Cell density was determined by CV staining. Hypoxic cell death was quantified by LDH release and PI staining. Mitochondial protein content was measured by Western Blotting. Oxygen consumption was determined with a fluorescence-based assay. Glucose concentration was measured in supernatants. Results: We report that doxycycline doses commonly used with inducible expression systems (0.01–1 µg/mL) substantially alter cellular metabolism: Mitochondrial protein synthesis was inhibited accompanied by reduced oxygen and increased glucose consumption. Furthermore doxycycline protected human glioma cells from hypoxia-induced cell death. An impairment of cell growth was only detectable with higher doxycycline doses (10 µg/mL). Conclusion: Our findings describe settings where doxycycline exerts effects on eukaryotic cellular metabolism, limiting the employment of Tet-inducible systems. Possible effects of doxycycline on cell metabolism have to be taken into consideration when employing such inducible systems.